Inhibition of (3)H-Uridine Uptake in Mouse Macrophages Infected with Mycobacterium lepraemurium - Ozato, Keiko (1972)
In mouse macrophages cultivated in vitro and infected with Mycobacterium lepraemurium, (3)H-uridine uptake was comparable to that in uninfected controls when cells were labeled immediately after infection but was markedly inhibited 2 to 3 hr later.